2020
DOI: 10.1016/j.ijid.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with hepatitis B and D virus infections among migrant sex workers in Chiangmai, Thailand: A cross-sectional study in 2019

Abstract: To determine the prevalence of hepatitis B surface antigen (HBsAg) and antibody to hepatitis delta virus (anti-HDV) and associated factors among migrant sex workers in Chiangmai, Thailand. Methods: This cross-sectional study was conducted at various sexual entertainment venues in Chiangmai, Thailand, in 2019. Consenting participants were interviewed using a questionnaire, and plasma was tested for hepatitis B virus (HBV) markers (DiaSorin, Italy) and anti-HDV antibody (DIA.PRO Diagnostic Bioprobes, Italy), if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 25 publications
4
19
0
9
Order By: Relevance
“…12,25,26 On the other hand, although mercenary sex was considered an important risk factor for HDV transmission in the 1990s, 27 it has not been reported in the literature of the last decade, except in a recent study from Thailand that found no HDV marker in HBsAgpositive migrant sex workers. 28 In Europe, the demise of HDV in domestic populations has been offset by new infections introduced by immigrants from areas where HDV remains endemic. 29 The relative proportion of HDV-infected migrants is increasing compared to HDV-infected native populations 30 ; migratory flows have interrupted the decline in infections, whose prevalence in HBsAg carriers stabilised in the last decade at 8-10% in Germany, Italy, Spain and France.…”
Section: Hdv Infection In Europe and The Usmentioning
confidence: 99%
“…12,25,26 On the other hand, although mercenary sex was considered an important risk factor for HDV transmission in the 1990s, 27 it has not been reported in the literature of the last decade, except in a recent study from Thailand that found no HDV marker in HBsAgpositive migrant sex workers. 28 In Europe, the demise of HDV in domestic populations has been offset by new infections introduced by immigrants from areas where HDV remains endemic. 29 The relative proportion of HDV-infected migrants is increasing compared to HDV-infected native populations 30 ; migratory flows have interrupted the decline in infections, whose prevalence in HBsAg carriers stabilised in the last decade at 8-10% in Germany, Italy, Spain and France.…”
Section: Hdv Infection In Europe and The Usmentioning
confidence: 99%
“… 10 From limited studies in Ethiopia, the highest prevalences were reported from Gondar (28.9%), 11 Mekelle (6%), 12 and Dessie (13.1%). 13 In other developed countries such as Brazil, 14 China, 15 Thailand, 16 and India 17 the prevalence of HBV among Female sex workers (FSWs) was 23.6%, 10.7%, 11.4%, and 3.6%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Their median age was 25 years (interquartile range: 22-30 years old), and 91.7% were Shan/Tai-Yai. Sociodemographic, health and medical histories, and sexual practices of the study population have been reported in a previous study [1]. Interestingly, a large majority (87.9%) reported always using condoms while having sex with their clients whereas 17% reported using condoms with their spouses.…”
Section: To the Editormentioning
confidence: 53%
“…Evidence of sexual transmission of HCV in this population remains limited. We conducted an analysis of HCV seroprevalence among a group of migrants working in the sex industry in Chiangmai, with a high prevalence of HBsAg [1] and assessed the risk factors for HCV infection.…”
Section: To the Editormentioning
confidence: 99%